Serum concentrations of Krebs von den Lungen-6 as prognostic biomarker in patients with silicosis - Raluca-Andreea Smărăndescu; Marina-Ruxandra Oțelea; Marina-Ruxandra Oțelea; Eugenia Panaitescu; Andrä Jitka; Francesco Bonella; Agripina Rașcu; Agripina Rașcu (Frontiers in Medicine, 2025)
IntroductionKL-6, a pneumocyte derived biomarker, is increased in patients with interstitial lung diseases (ILDs). We aimed to investigate the role of serum KL-6 as a diagnostic and prognostic biomarker in silica-exposed workers.Material and methodWe studied 108 silica-exposed subjects and 25 healthy controls. Chest radiography (CXR), pulmonary function tests, inflammatory markers were collected. Progressive massive fibrosis (PMF) was defined according to the ILO classification. KL-6 was measured in serum by fully automated CLEIA at first presentation at our institution, intended as baseline visit, with a time point from the initial exposure variable for each patient.ResultsPMF was present in 23 subjects. Serum KL-6 levels were significantly higher in subjects with PMF than in controls, exposed workers or simple silicosis (p<0.001). In PMF, serum KL-6 positively correlated with C-reactive protein (CRP) and Erythrocyte sedimentation rate (ESR), and negatively with forced vital capacity (FVC) % predicted. At a cut-off of 436 U/mL, serum KL-6 differentiated exposed workers from PMF with a specificity and sensitivity exceeding 90% (p<0.0001), while a cut-off of 445 U/mL differentiated simple silicosis from PMF (p<0.0001). In the multivariate analysis, serum KL-6 levels were independently associated with risk of fibrosis.ConclusionSerum KL-6 appears to be a promising biomarker for the occurrence and progression of PMF in silica-exposed workers.